Schoology-based Blended Learning in Academic Writing Class during the COVID-19 Pandemic - Prihandoko, Lastika Ary (Jurnal Pendidikan Indonesia, 2022)
The COVID-19 is a global disease that has an enormous impact on almost every field, including the educational sector. The shifting of face-to-face learning to blended learning during the COVID-19 pandemic requires technological tools to support the learning process. Hence, this research explores the implementation of Schoology as a learning management system in academic writing class during the COVID-19 crisis. A sequential mixed-method is applied in this research by analyzing data qualitatively and quantitatively. All students in an academic writing class were chosen as participants using the total sampling technique. Furthermore, the research instruments consisted of guided interviews and close-ended questionnaires distributed using google form. The results reveal that Schoology is beneficial to be infused with blended learning. The Schoology platform stimulates students who have sufficient online learning readiness to positively perceive their learning experience using Schoology-based blended learning. However, the institutional intervention must be implemented to provide students training to improve digital competencies, strategies for becoming independent learners, and time management.Â